Effect of Corruption on Social Service Delivery in Public Institutions of Uganda: The Case of Mbale District Local Government - Doreen Anthony Saano (Uganda Christian University, 2024)
The study explored the effect of corruption on the social service delivery in Mbale district local government (BDLG). Also the specific objectives of the study were; to examine the relationship between bribe, nepotism, favouritism and service delivery of BDLG. A cross section research was carried out which involved the use of quantitative analysis. Data was collected by the use of questionnaires and interview guides. The study sampled 80 respondents from four sub counties out of 100 of targeted populations. The sample size was determined using Sample size determination (Krejcie & Morgan, 1970). Data was analysed using SPSS. 16. Oversion. The data was analysed using both descriptive and inference statistics where it concluded about the variables with respect to the objectives. The coefficient of correlation between corruption and social service delivery was positively low (0.0 187). The study further found out that there was a negative relationship between corruption and social service delivery. The researcher recommends the government to always carry out department4l performance reviews and the ministry should carry out an assessment of the procedures/processes with the aim of identifying